2014
DOI: 10.1093/nar/gku237
|View full text |Cite
|
Sign up to set email alerts
|

Human MUS81-EME2 can cleave a variety of DNA structures including intact Holliday junction and nicked duplex

Abstract: MUS81 shares a high-degree homology with the catalytic XPF subunit of the XPF–ERCC1 endonuclease complex. It is catalytically active only when complexed with the regulatory subunits Mms4 or Eme1 in budding and fission yeasts, respectively, and EME1 or EME2 in humans. Although Mus81 complexes are implicated in the resolution of recombination intermediates in vivo, recombinant yeast Mus81-Mms4 and human MUS81-EME1 isolated from Escherichia coli fail to cleave intact Holliday junctions (HJs) in vitro. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
0
35
2
Order By: Relevance
“…This second result is also different from what has been described for budding yeast Mus81‐Mms4, which is maximally active towards model RFs when immunoprecipitated from cells synchronized in mitosis . While more work will be required to clarify this apparent discrepancy, it is important to consider that human MUS81 binds not only EME1 but also a second orthologs of Mms4, EME2, which is known to enhance the activity and decrease the specificity of MUS81 . Hence, high activity of MUS81 immunoprecipitates towards model RFs during S‐phase may simply reflect the constitutive association with EME2, which could conceal the fluctuating activity of MUS81‐EME1‐SLX4.…”
Section: Cell Cycle Regulation Of Human Mus81contrasting
confidence: 57%
See 1 more Smart Citation
“…This second result is also different from what has been described for budding yeast Mus81‐Mms4, which is maximally active towards model RFs when immunoprecipitated from cells synchronized in mitosis . While more work will be required to clarify this apparent discrepancy, it is important to consider that human MUS81 binds not only EME1 but also a second orthologs of Mms4, EME2, which is known to enhance the activity and decrease the specificity of MUS81 . Hence, high activity of MUS81 immunoprecipitates towards model RFs during S‐phase may simply reflect the constitutive association with EME2, which could conceal the fluctuating activity of MUS81‐EME1‐SLX4.…”
Section: Cell Cycle Regulation Of Human Mus81contrasting
confidence: 57%
“…One surprising finding arising from the analysis of chromosome breakage upon inhibition of WEE1 was its exquisite dependency on EME2. As discussed above, a key difference between MUS81‐EME2 and MUS81‐EME1 is that MUS81‐EME2 has weaker substrate specificity in vitro and overall higher nuclease activity . A second difference is cellular abundance in cells: EME2 is expressed at lower levels and only ~ 20% of all MUS81 associated with EME2, while the remaining 80% bind EME1 .…”
Section: Cell Cycle Regulation Of Human Mus81mentioning
confidence: 99%
“…The C-terminal regions of EME1 (total of 570 residues) and EME2 (total of 379 residues) are highly homologous with more than 60% sequence similarity in human (43,44). Multiple studies have suggested that these complexes are involved in maintenance of genomic stability and damaged DNA processing (43)(44)(45)(46)(47). Purified recombinant MUS81-EME1 recognizes and preferentially cleaves several DNA structures, including 3Ј-flap, aberrant replication forks, and nicked Holliday junctions (45,48).…”
mentioning
confidence: 99%
“…EME1 is nonetheless required for the stability and activity of the MUS81-EME1 complex, and acts as a regulatory subunit. MUS81 also interacts with EME2, to form the MUS81-EME2 nuclease [27][28][29], but this appears to be dispensable for the resolution of recombination intermediates [30]. Ti BS Figure 1.…”
mentioning
confidence: 99%